Кыргызско-алтайский шаманизм: аспекты сравнительно-исторического анализа - Исаева, А.А. (Изд-во КарГУ, 2012)
Дүниетаным мен магия-діни рəсімдер төңірегінде далалық зерттеулерге сүйенсек, кейбір қырғыз тұрғындарының бөлігі (басым бөлігі орта жəне егде жастағы əйелдер) əлі күнге дейін алтаймен параллелі бар, шаманизм элементтерінен көрініс алуын жалғастырып келеді. Алтай шаманизмінің ма- териалдарын қолдану салыстырмалы-тарихи талдау барысында бізге құнды ақпараттарды алу мүмкіндігін тудырады, қырғыз шаман дінінде туындайтын бірқатар сұрақтардың шешімі мен олардың ерекшеліктеріндегі маңызды жəне сенімді көзі болып табылады. According to the field researches, in the world view and magic-religious practices of some part of Kyrgyz population (mostly women of the average and elderly age) there are still some elements of shamanism, that has parallels with the Altay one. For the purpose of deeper knowledge of essence and orientation of spiritual processes, people address to the ancient and archaic forms of knowledge shown in religious representations, ceremonies and customs. The comparative-historical analysis with the use of some materials on the Altay shamanism gives us an opportunity to reveal the valuable data, which could be used to solve some issues regarding the shamanist religion of the Kyrgyz people and its specifics.
Keywords: Кыргызский шаманизм; Алтай; Шаманизм